An illustrated checklist of Stratiomyidae (Diptera: Brachycera) from Paraguay, with three new synonyms and 22 new records of species for the country - Fachin, Diego Aguilar; Zichinelli, Marcela Maria Parada; Barrett, Bolívar Rafael Garcete (Zootaxa, 2022)
The Stratiomyidae (Diptera) of Paraguay is cataloged and illustrated, and information is given on distributions, name-bearing types, synonyms, and pertinent literature. Previously to this study, the fauna of soldier flies in the country comprised 18 genera and 29 species, which has been raised up to 35 genera and 63 species, of which only nine are assigned to morphospecies level. The list of species is based on the examination of the original descriptions of all nominal species, all other references known to us containing taxonomic and distributional information, and new material examined from various collections. Images of 45 species are herein provided, which include type specimen images of seven valid species, of which three are exclusively found in the country. One subfamily is newly reported from Paraguay: Chrysochlorininae. Fourteen genera are newly reported from Paraguay: Acanthinomyia Hunter, 1900; Archistratiomys Enderlein, 1913; Auloceromyia Lindner, 1969; Chrysochlorina James, 1939; Gowdeyana Curran, 1928; Hoplitimyia James, 1934; Leucoptilum James, 1943; Neoberis Lindner, 1949; Myxosargus Brauer, 1882; Nothomyia Loew, 1869; Panacris Gerstaecker, 1857; Promeranisa Walker, 1854; Psellidotus Rondani, 1863; and Raphiocera Macquart, 1834. Twenty-two species are newly reported from Paraguay: Acanthinomyia elongata (Wiedemann, 1824); Archistratiomys rufipalpis (Wiedemann, 1830); Auloceromyia pedunculata Pimentel & Pujol-Luz, 2000; Chordonota inermis (Wiedemann, 1830); Chrysochlorina albipes James, 1939; Chrysochlorina incompleta (Curran, 1929); Gowdeyana vitrisetosus (Lindner, 1935); Hermetia flavipes Wiedemann, 1830; Hermetia pulchra Wiedemann, 1830; Hermetia teevani Curran, 1934; Leucoptilum plaumanni James, 1943; Merosargus cingulatus Schiner, 1868; Merosargus coxalis Lindner, 1949; Merosargus golbachi James in James & McFadden, 1971; Merosargus nebulifer James in James & McFadden, 1971; Merosargus obscurus (Wiedemann, 1830); Merosargus stigmaticus (Lindner, 1949); Neoberis brasiliana Lindner, 1949; Panacris nigribasis Lindner, 1949; Promeranisa nasuta (Macquart, 1850); Raphiocera armata (Wiedemann, 1830); and Sargus thoracicus Macquart, 1834. Four species are removed from the Paraguayan fauna: Cyphomyia albitarsis (Fabricius, 1805), Euryneura pygmaea (Bellardi, 1862), and Nemotelus niger Bigot, 1879 have no specimens known from Paraguay, so the inclusion of Paraguay in their distribution is a typing error; and Nemotelus eburneopictus James (1974) has its type locality corrected to Argentina. The examination of the material allows the proposition of three specific synonyms: Cyphomyia imitans Curran, 1925 syn. nov. of C. gracilicornis Gerstaecker, 1857, Panacris breviseta Lindner, 1964 syn. nov. of P. nigribasis Lindner, 1949, and Dicranophora brevifurca James, 1943 syn. nov. of Dicamptocrana jorgenseni Frey, 1934 (this species is newly recorded to Brazil, state of São Paulo), after removing D. brevifurca out of synonymy with Dicranophora bispinosa (Wiedemann, 1830). Additionally, a female lectotype is designated for Rhingiopsis enderleini Lindner, 1928.